Preparation method of high-performance polyethylene / glass fiber composite material and application of high-performance polyethylene / glass fiber composite material in modified polypropylene
By blending polyethylene-glass fiber composite with polypropylene, the problem of poor mechanical properties of modified polypropylene is solved, and the mechanical properties of new composite materials are improved and application expansion is achieved.
Patent Information
- Application Number
- CN202411685106.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-22
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-11-22
AI Technical Summary
Existing modified polypropylene (PP) materials have poor mechanical properties and are difficult to meet the wider application needs.
By preparing polyethylene-glass fiber composite material and blending it with polypropylene, a new material with macroscopic uniformity and microscopic phase separation is formed to improve its mechanical properties.
The compressive ductility and mechanical properties of polypropylene have been significantly improved, forming a new composite material with excellent compressive ductility, expanding the application range of polyolefin composite materials.
Smart Images

Figure CN119505045A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of olefin polymerization and material modification, and relates to a preparation method of a high-performance polyethylene / glass fiber composite material and an application of the composite material in modified polypropylene. Background Art
[0002] Polyolefins are the most in-demand and highest-yield polymers in the world. They are widely used in various fields because of their abundant and cheap raw materials, light weight, good processing and molding properties, and good chemical corrosion resistance. Common polyolefins include polyethylene, polypropylene, polybutene, polybutadiene, ethylene-olefin copolymers, and ethylene-cycloolefin copolymers. At present, the global production of polyolefins has exceeded 400 million tons / a, most of which are polyethylene and polypropylene. High-end polyolefins (such as ethylene-olefin copolymers and ethylene-cycloolefin copolymers) have excellent performance and high added value, and have become the research focus of new polyolefin products. Catalysts have a crucial impact on the structure, performance and production capacity of polyolefins, especially in the research and development of high-end polyolefins.
[0003] Fiberglass is an inorganic non-metallic material with excellent performance. It has many types. Its advantages are good insulation, strong heat resistance, good corrosion resistance and high mechanical strength, but its disadvantages are brittleness and poor wear resistance. It is made of six kinds of minerals, namely pyrophyllite, quartz sand, limestone, dolomite, colemanite and magnesia borax, through high-temperature melting, wire drawing, winding and weaving. The diameter of its single filament is from several microns to more than 20 microns, which is equivalent to 1 / 20-1 / 5 of a hair. Each bundle of fiber strands is composed of hundreds or even thousands of single filaments.
[0004] Polypropylene (PP for short) is one of the most widely used general-purpose plastics. Crystalline polypropylene was produced in 1951, but the high crystallinity also caused PP to have disadvantages such as poor low-temperature toughness, large molding shrinkage and high notch sensitivity, which to a certain extent limited its wider application. Blending modification is the most effective way to toughen PP, and PP / PE blends have been developed since then. It uses the compatibility or reaction blending principle between components to mechanically blend two or more polymers with additives at a certain temperature, and finally forms a new material that is uniform in the macroscopic and phase-separated in the microscopic. Through the blending modification of PP, the shortcomings of brittleness at paper temperature, easy aging, and poor weather resistance are overcome, and its comprehensive performance is greatly improved. It has entered the field of engineering plastics and has become a strong rival of general engineering plastics and alloys.
[0005] The Chinese patent application document with publication number CN104861295A discloses a method for preparing a modified polypropylene material with improved impact strength. The preparation method is prepared by blending and modifying the raw materials including the following components in a one-step method: 100 parts of polypropylene, 20-40 parts of a main modifier, 2.5-10 parts of a secondary modifier, 0.5-5 parts of a cross-linking modifier, and 0.5-5 parts of a cross-linking auxiliary agent, wherein the main modifier is a polyolefin elastomer, the secondary modifier is a high-density polyethylene, the cross-linking modifier is an organic peroxide, and the cross-linking auxiliary agent is a divinylbenzene with a content of 50%-60%. The decomposition temperature of the cross-linking modifier when the half-life is 1 minute is 1-5°C different from the melting temperature of PP. This patent can greatly improve the impact strength of the modified PP, and give the composite material excellent impact resistance, rigidity, aging resistance, cold resistance and gasoline resistance. At the same time, the other properties are almost unaffected. However, the mechanical properties of the modified polypropylene (PP) material prepared by this patent are still poor and need to be further improved. Summary of the invention
[0006] The technical problem to be solved by the present invention is how to solve the problem of poor mechanical properties of existing modified polypropylene (PP) materials.
[0007] The present invention solves the above technical problems through the following technical means:
[0008] A first aspect of the present invention provides a method for preparing a polyethylene-glass fiber composite material, comprising the following steps:
[0009] Glass fiber, toluene, nickel diimide catalyst, and Et2AlCl are added to a reaction container under N2 environment, and ethylene gas is introduced to carry out polymerization reaction to obtain the nickel diimide catalyst.
[0010]
[0011] Toluene is used as the reaction solvent, and Et2AlCl (diethylaluminum monochloride) acts as a co-catalyst.
[0012] Preferably, the usage ratio of the glass fiber, the diimine nickel catalyst and Et2AlCl is (1.0-4.5) g: (1-3) μmol: (300-500) μmol, and more preferably 2.5 g: 2 μmol: 400 μmol.
[0013] Preferably, the polymerization reaction temperature is 30-60° C., and the polymerization reaction time is 0.3-1 h.
[0014] The second aspect of the present invention provides a polyethylene-glass fiber composite material prepared by the above preparation method.
[0015] The third aspect of the present invention provides a modified PP material, which is composed of the following raw materials in parts by weight: 65-100 parts of polypropylene, 5-30 parts of modified filler and 0.1-0.5 parts of antioxidant; the modified filler is the above-mentioned polyethylene-glass fiber composite material.
[0016] Preferably, the antioxidant is one or more of Irganox1010, antioxidant 168, and antioxidant 1076.
[0017] A fourth aspect of the present invention provides a method for preparing the modified PP material, comprising the following steps:
[0018] The polypropylene, modified filler and antioxidant are mixed evenly according to the weight ratio, melted and extruded to obtain the product.
[0019] The fifth aspect of the present invention provides a diimine ligand having the structural formula
[0020]
[0021] The sixth aspect of the present invention provides a nickel diimide catalyst, the chemical formula of which is as follows:
[0022]
[0023] A seventh aspect of the present invention provides a method for preparing the above-mentioned nickel diimide catalyst, comprising the following steps:
[0024] (1) 4,4-difluorobenzhydrol (bis(4-fluorophenyl)methanamine) and [1,1'-biphenyl]-2-amine are mixed, heated for a period of time, and then zinc chloride (ZnCl2) dissolved in hydrochloric acid (HCl) is added to react to obtain compound (I);
[0025] (2) reacting compound (I) with anthraquinone to obtain compound (II);
[0026] (3) Compound (II) is then reacted with 2,6-dimethylaniline to obtain compound (III);
[0027] (4) Under a nitrogen atmosphere, compound (III) is reacted with (DME)NiBr2 to obtain a diimine nickel catalyst
[0028]
[0029] The synthetic route is as follows:
[0030]
[0031] Preferably, in step (3), the molar ratio of compound (II) to hexadecylamine is 1:1.
[0032] Preferably, the heating temperature in step (1) is 80-100°C.
[0033] Preferably, the reaction time in step (1) is 2 hours.
[0034] Preferably, the reaction time in step (2) is 10-14 h.
[0035] Preferably, the reaction time in step (3) is 10-14 h.
[0036] Preferably, the reaction time in step (4) is 3 h.
[0037] The eighth aspect of the present invention provides the use of the above-mentioned diimine nickel catalyst in olefin polymerization.
[0038] The beneficial effects of the present invention are:
[0039] 1. The present invention is based on a diimine nickel catalyst with a special structure. The structure of the catalyst has a very special spatial structure. Because the spatial structure of the catalyst presents a dual coordination structure, it has a larger specific surface area, and the changes in the coordination number and valence electron state of the surface nickel atoms make the catalyst extremely active. Because the large steric hindrance of the catalyst in space is in the same direction, it has a certain conjugation effect, which further improves the activity of the catalyst, and the catalyst also maintains a certain stability. Therefore, polyethylene is prepared using its high activity performance, and toughening experiments are carried out on the prepared polyethylene, and the obtained polyethylene-glass fiber composite material is applied to polypropylene. Thereby realizing a new composite material with excellent compressive ductility, it also improves a new output path for the diversified development of polyolefin composite materials. It also provides a new way for the synthesis method of polyolefin composite materials.
[0040] 2. The main catalyst α-diimine asymmetric nickel complex used in the composite material of the present invention is characterized in that the catalyst structure is dual-coordinated and simultaneously forms a "large, small, and small" arrangement structure. The catalyst is special due to the electronic effect and steric effect between atoms in the arrangement structure and the effect of ππ conjugation. Therefore, the ligand that provides electrons may have higher activity. Therefore, the catalyst used in the present invention has extremely high polymerization activity under the promotion of the "large, small, and small" structure. At the same time, in theory, the catalyst structure should be "large, small, and small", that is, the large steric hindrance and the small steric hindrance groups are staggered and separated. However, the large steric hindrance of the catalyst is located in one direction, and the small steric hindrance is located in one direction, while also maintaining high activity and stability.
[0041] 3. The present invention provides a new polyolefin composite material, namely, a polyethylene-glass fiber composite material. The polyethylene of the composite material is obtained by catalyzing ethylene polymerization with the above catalyst, and the polyethylene-glass fiber has certain mechanical properties and also ensures its high elasticity.
[0042] 4. The modified (PP) in the present invention is blended with polyethylene-glass fiber composite material into polypropylene to form a new polyolefin composite material that is uniform in macroscopic terms and phase-separated in microscopic terms. Adding a small amount of polyethylene-glass fiber elastomer can improve certain mechanical properties of polypropylene.
[0043] 5. Based on the modified PP material, the present invention uses polyethylene-glass fiber composite material as a filling material to prepare a new composite material with high elasticity and high strength. BRIEF DESCRIPTION OF THE DRAWINGS
[0044] Figure 1 The compound (III) of Example 1 of the present invention 1 H NMR spectrum;
[0045] Figure 2 The compound (III) of Example 1 of the present invention is 13 C NMR spectrum;
[0046] Figure 3 is an X-Ray Crystallography image of the diimine nickel catalyst of Example 1 of the present invention;
[0047] Figure 4 cyclic stress-strain curves of polyethylene-glass fiber composite materials prepared in Examples 2 to 5 of the present invention;
[0048] Figure 5 This is a scanning electron microscope image of the polyethylene-glass fiber composite material prepared in Example 2 of the present invention;
[0049] Figure 6 The tensile strength and impact resistance test diagram of the modified PP material prepared in Examples 6 to 10 of the present invention;
[0050] Figure 7 This is a test chart of the tensile properties of the modified PP materials prepared in Examples 6 to 10 of the present invention. DETAILED DESCRIPTION
[0051] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0052] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention.
[0053] Unless otherwise specified, the test materials and reagents used in the following examples can be obtained from commercial sources.
[0054] If no specific techniques or conditions are specified in the examples, they can be carried out according to the techniques or conditions described in the literature in the art or according to the product instructions.
[0055] The product performance test conditions of the following examples and comparative examples are as follows:
[0056] The tensile strength test used a tensile specimen model of (50.0±5.0)mm*(4.0±0.5)mm*(2.5±0.2)mm, with a tensile rate of 50mm / min;
[0057] The cantilever beam notched impact strength test uses a cantilever beam notched impact strength specimen model of (80.0±5.0)mm*(10.0±0.5)mm*(4.0±0.2)mm. The notch is machined by a milling machine, and the notch depth is (2.0±0.2)mm.
[0058] Embodiment 1:
[0059] A method for preparing a nickel diimide catalyst, the technical route of which is as follows:
[0060]
[0061] The specific steps include:
[0062] (1) Synthesis of compound (I): 4,4-difluorobenzhydrol (13.153 g; 60 mmol) and benzidine (5.076 g; 30 mmol) were mixed and heated to 120°C, and then zinc chloride (2 g) (ZnCl2) dissolved in an appropriate amount of hydrochloric acid (HCl) was added, and the reaction was carried out to obtain compound (I). The reaction formula is as follows:
[0063]
[0064] (2) Synthesis of compound (II): Add acetic acid (8 ml) to a mixture of the above compound I (5.736 g; 10 mmol) and acenaphthenequinone (1.82 g; 10 mmol). Heat to 80°C, stir for 30 min, add acetonitrile (10 ml), and react for 24 hours. Cool the reaction mixture to room temperature and extract with CH2Cl2. Wash the combined organic layer with brine and dry over anhydrous Na2SO4. Remove the solvent under reduced pressure to obtain a crude product, which is then purified by flash silica chromatography (EA / PE=1 / 10 (volume ratio)). The desired compound (II) is obtained, and the reaction formula is as follows:
[0065]
[0066] (3) Synthesis of compound (III): Compound (II) (7.38 g; 10 mmol) and hexadecylamine (1.21 g; 10 mmol) were heated to 120°C, toluene (30 ml) solution was slowly added, and the mixture was stirred for 30 min. PTSA (0.5 g) (p-toluenesulfonic acid) was added, and then the mixture was heated to 80°C and reacted for 24 h. The reactant was cooled to room temperature, extracted three times with CH2Cl2, and dried with anhydrous magnesium sulfate. The magnesium sulfate was filtered off, the filtrate was concentrated, and the compound (III) was obtained by column chromatography. The reaction formula is as follows: (Compound (III)) 1 HNMR spectrum, 13 C NMR spectrum Figure 1 , Figure 2 (shown)
[0067]
[0068] (4) Synthesis of compound (IV): Under nitrogen atmosphere, compound (III) (0.85 g, 1.0 mmol) synthesized in step (3) was reacted with (DME)NiBr (0.31 g, 1.0 mmol) in CH2Cl2 (20 mL) solvent for 6-12 h. The mixture was filtered, washed and dried to obtain a nickel diimide catalyst with an acenaphthenequinone skeleton (i.e., compound (IV)). The reaction formula is as follows:
[0069]
[0070] X-Ray Crystallography of compound (IV) Figure 3 shown.
[0071] Selected bond lengths and angles[deg]:Br(1)-Ni(1)=2.4144(16),Br(2)-Ni(1)=2.4592(13),Br(3)-Ni(2)=2.4637(13)Br(4)-Ni(2)=2.3959(16);Ni(1)-N(1) )=2.059(6),Ni(1)-N(2)=2.130(2),Ni(2)-N(3)=2.070(6),Ni(2)-N(4)=2.134(6),N(1)-C(62)=1.452(9),N(1)-C(98)=1.282(10),
[0072] N(2)-C(97)=1.290(10),N(2)-C(109)=1.457(9);N(3)-C(9)=1.256(5),N(3)-C(7)=1.462(9),N(4)-C(10)
[0073] =1.292(10)N(4)-C(31)=1.464(9);Ni(2)-Br(3)-Ni(1)=92.04(4),N(1)-Ni(1)-Br(2)=155.06(18),
[0074] N(1)-Ni(1)-Br(1)=103.75(17),N(1)-Ni(1)-N(2)=95.99(19),Br(3)-Ni(2)-Br(2)=87.71(5),Br(4)-Ni(2)-Br(3)
[0075] =100.09(5),Br(4)-Ni(2)-Br(2)=99.72(5),N(3)-Ni(2)-Br(3)=159.20(19),N(3)-Ni(2)-Br(2)=93.22(17),N(3)-Ni(2)-Br(4)=100.22(19),N(3)-Ni(2)-N(4)=7 9.5(2),N(4)-Ni(2)-Br(3)=91.77(17);N(4)-Ni(2)-Br(2)=157.29(18),N(4)-Ni(2)-Br(4)=107.72(18),C(9)-N(3)-Ni(2)=113.4(5),C(9)-N(3)-C(7)=116.1(6),
[0076] C(7)-N(3)-Ni(2)=130.5(5),C(10)-N(4)-Ni(2)=113.2(5),C(10)-N(4)-C(31)=117.7(7),C(31)-N(4)-Ni(2)
[0077] =128.8(5); C(62)-N(1)-Ni(1)=127.5(5); C(98)-N(1)-Ni(1)=114.3(5); C(98)-N(1)-C(62)=
[0078] 118.0(6); C(97)-N(2)-Ni(1)=129.6(5); C(97)-N(2)-C(109)=118.8(6); C(109)-N(2)-Ni(1)=129.6(5)
[0079]
[0080]
[0081] Embodiment 2:
[0082] A method for preparing a polyethylene-glass fiber composite material comprises the following steps: glass fiber (2.5 g), Et2AlCl (400 μmol), toluene (28 mL) and a magnetic stirring bar are placed in a 350 mL thick-walled glass pressure container in a glove box. The pressure container is connected to a high-pressure polymerization line to degas the solution. The container is heated to 40° C. using an oil bath and allowed to equilibrate for 5 minutes. A nickel diimide catalyst (2 μmol, prepared in Example 1) in CH2Cl2 (2 mL) is injected into the container using a syringe. Under rapid stirring, the reactor is pressurized and maintained at 8.0 atmospheres of ethylene. After 20 minutes, the container is vented, the polymer is precipitated in acidified ethanol (ethanol / HCl=50:1 (volume ratio)), and dried under vacuum at 50° C. for 24 hours to obtain a polyethylene-glass fiber composite material.
[0083] The scanning electron microscope image of the polyethylene-glass fiber composite material prepared in this embodiment is as follows: Figure 5 As shown, it can be seen that the materials are mixed evenly.
[0084] Embodiment 3:
[0085] The difference between this embodiment and embodiment 2 is that the glass fiber is 1.0g, and the rest is the same as embodiment 2.
[0086] Embodiment 4:
[0087] The difference between this embodiment and embodiment 2 is that the glass fiber is 3.5g, and the rest is the same as embodiment 2.
[0088] Embodiment 5:
[0089] The difference between this embodiment and embodiment 2 is that the glass fiber is 4.5g, and the rest is the same as embodiment 2.
[0090] The cyclic stress-strain curves of the polyethylene-glass fiber composite materials obtained in Examples 2 to 5 are shown in FIG. Figure 4 As shown in the figure, it can be seen that with the increase of glass fiber incorporation, the tensile strength of polyethylene-glass fiber (modified filler) first increases and then decreases. Example 2 can increase its tensile strength to 6.23 MPa without affecting the tensile elongation of the filler, making it convenient for the subsequent modification of polypropylene (pp).
[0091] Example 6: (Polyethylene-glass fiber composite material dosage 10%)
[0092] A method for preparing a modified PP material: 90 parts of polypropylene, 10 parts of polyethylene-glass fiber composite material (prepared in Example 2), and 0.2 parts of antioxidant Irganox168 are weighed by weight, and added into a mixer for mixing for 10 minutes to obtain a mixture; the mixture is added into a twin-screw extruder, and the modified PP material is obtained by melting and extruding, wherein the temperature and screw speed of each zone of the twin-screw extruder are respectively: the upper cavity plate temperature is 140°C, the lower cavity plate temperature is 160°C, and the screw speed is 130-180r / min.
[0093] Example 7: (doping amount 5%)
[0094] The difference between this embodiment and embodiment 6 is that: 95 parts of polypropylene, 5 parts of polyethylene-glass fiber composite material, and other steps are the same as embodiment 6.
[0095] Example 8: (doping amount 15%)
[0096] The difference between this embodiment and embodiment 6 is that: 85 parts of polypropylene, 15 parts of polyethylene-glass fiber composite material, and other steps are the same as embodiment 6.
[0097] Example 9: (doping amount 20%)
[0098] The difference between this embodiment and embodiment 6 is that: 80 parts of polypropylene, 20 parts of polyethylene-glass fiber composite material, and other steps are the same as embodiment 6.
[0099] Example 10: (doping amount 25%)
[0100] The difference between this embodiment and embodiment 6 is that: 75 parts of polypropylene, 25 parts of polyethylene-glass fiber composite material, and other steps are the same as embodiment 6.
[0101] Comparative Example 1: (dosage 30%)
[0102] The difference between this comparative example and Example 6 is that: 70 parts of polypropylene, 30 parts of polyethylene-glass fiber composite material, and other steps are the same as Example 6.
[0103] Comparative Example 2: (dosage 35%)
[0104] The difference between this comparative example and Example 6 is that: 65 parts of polypropylene, 35 parts of polyethylene-glass fiber composite material, and other steps are the same as Example 6.
[0105] Comparative Example 3: (dosage 0%)
[0106] The difference between this comparative example and Example 6 is that no polyethylene-glass fiber composite material is added, and the other steps are the same as Example 6.
[0107] The modified PP materials obtained in Examples 6 to 10 and Comparative Examples 1 to 3 were injection molded into strips by an injection molding machine for tensile performance testing. The test results are shown in the following table:
[0108]
[0109] The “—” in the table means that the material morphology is poor and it is impossible to prepare samples for testing.
[0110] It can be seen from the above table that when the doping content of polyethylene-glass fiber composite material is within 25%, the modified PP material can be blended evenly and has good performance, but when the doping content reaches more than 30%, the composite material will have problems such as uneven mixing, the compatibility will deteriorate, and it cannot be tested.
[0111] The tensile strength and impact resistance test results of the modified PP materials prepared in Examples 6 to 10 are as follows: Figure 6 The tensile properties test results are shown in Figure 7 As shown. Figure 6 It can be seen that with the increase of modified filler, the tensile strength of modified polypropylene (PP) has a trend of first increasing and then decreasing. When the addition amount is 10%, its tensile strength reaches the highest.
[0112] from Figure 7 It can be seen that when the modified filler is added in an amount of 10%, the tensile strength of polypropylene (PP) can be increased by 2.41 times without affecting the tensile elongation of the polypropylene (PP).
[0113] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing a polyethylene-glass fiber composite material, characterized in that: The following steps are involved: Glass fiber, toluene, nickel diimide catalyst, and Et2AlCl are added to a reaction container under N2 environment, and ethylene gas is introduced to carry out polymerization reaction to obtain the nickel diimide catalyst.
2. The preparation method according to claim 1, characterized in that: The usage ratio of the glass fiber, the nickel diimide catalyst and Et2AlCl is (1.0-4.5) g: (1-3) μmol: (300-500) μmol.
3. The preparation method according to claim 1, characterized in that: The polymerization reaction temperature is 30-60° C., and the polymerization reaction time is 0.3-1 h.
4. The polyethylene-glass fiber composite material obtained by the preparation method according to any one of claims 1 to 3.
5. A modified PP material, characterized in that: The composite material is composed of the following raw materials in parts by weight: 65-100 parts of polypropylene, 5-30 parts of modified filler and 0.1-0.5 parts of antioxidant; the modified filler is the polyethylene-glass fiber composite material as claimed in claim 4.
6. The modified PP material according to claim 5, characterized in that: The antioxidant may be one or more of Irganox1010, antioxidant 168 and antioxidant 1076.
7. A diimine ligand, characterized in that: Its structural formula is 8. A nickel diimide catalyst, characterized in that: Its structural formula is 9. The method for preparing the diimine nickel catalyst according to claim 8, characterized in that: The following steps are involved: (1) 4,4-difluorobenzhydrol and benzidine are mixed, heated for a period of time, and then zinc chloride dissolved in hydrochloric acid is added to react to obtain compound (I); (2) reacting compound (I) with acenaphthenequinone to obtain compound (II); (3) reacting compound (II) with hexadimethoxane to obtain compound (III); (4) Under a nitrogen atmosphere, compound (III) is reacted with (DME)NiBr2 to obtain a diimine nickel catalyst 10. Use of the diimine nickel catalyst according to claim 8 in olefin polymerization.
Citation Information
Patent Citations
Naphthalene nucleus containing alpha-diketiminato nickel (II) composition as well as preparation method and application thereof
CN102050840A
Fluorine-containing alpha-diimine nickel coordination compounds for preparing polyolefin elastomer, intermediate, preparation method and application thereof
CN111303215A
Modified PP material and preparation method thereof
CN115466461A
Preparation methods of modified PP material, branched polyethylene elastomer and bamboo-plastic composite material
CN117777594A
Catalyst containing large-volume diimine nickel as well as preparation method and application of catalyst
CN117946185A